Tax Morale: Utilising behavioural insights to improve tax compliance in South Africa - Meyer, Aneeqah (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, there is a significant tax gap due in large part to the non-compliance of personal income taxpayers. This study seeks to deliver proposals that would reduce that tax gap by increasing tax compliance through the improvement of tax morale. Noting that the use of behavioural techniques to achieve policy outcomes has seen considerable success in recent years, there has been an increase in uptake of behavioural techniques being used by policy makers to increase tax compliance (and tax morale). While studies have indicated the types of behavioural insights that may be relevant to increase tax compliance, what has been missing from these discussions is a detailed analysis of how current domestic legislation and policy should be amended. This dissertation analyses how behavioural tools could be implemented to increase tax morale within the South African taxation framework. To do so, it considers empirical evidence to determine drivers of tax morale within South Africa. With reference to these drivers, this dissertation presents legislative and policy changes that could be made to influence taxpayers’ intrinsic motivation to pay taxes and, through this mechanism, improve national voluntary tax compliance.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; tax; tax morale; tax compliance; law; behavioural economics; tax administration; SDG-8: Decent work and economic growth